The In-vitro and In-vivo Evaluation of Tiamulin and Tilmicosin for the Treatment of Mycoplasma gallisepticum Infected Broiler Chickens - El-Ghany, Wafaa A. Abd (International Journal of Poultry Science, 2009)
This study was undertaken to evaluate the efficacy of some antimicrobials containing tiamulin and tilmicosin (as active principles) against Mycoplasma gallisepticum (MG) infection both in-vitro and in-vivo. For in-vitro investigation, the Minimum Inhibitory Concentration (MIC) of tiamulin and tilmicosin against MG organism was done. However, the in-vivo evaluation of tiamulin and tilmicosin against field MG infection was carried out on a commercial broiler chicken farm taken from MG infected farm and proved to have such infection through bacteriological and serological examination at day old. Once the birds suffered from respiratory signs at 22 days of age, this flock was divided into three separate houses. Chickens in house (1) were kept as MG-infected without treatment; chickens in the house (2) were treated with tiamulin in the drinking water (1 gram/1.5 liter) for 3 successive days and the birds in house (3) were also treated with tilmicosin in the drinking water (0.3 ml/liter) for 3 successive days. Just after appearance of the first clinical signs and mortalities, the clinical signs score was recorded, the birds were weighed and the serum samples were collected for serological examination. The clinical signs and the mortalities in each house were recorded daily during and after the treatment course till the end of the study (42 days of age). The body weight of the birds in each house was determined weekly till 6 weeks of age. Twenty birds from each house were sacrificed weekly for recording the air-sac lesion score and for re-isolation of MG. The air-sac lesion score and the re-isolation of MG were also detected from the dead birds. Serum samples were collected from sacrificed 20 birds just after appearance of clinical signs and from each house at the end of the work (42 days of age) for detecting the presence of antibodies for MG infection using serum plate agglutination test. The results of the in-vitro assessment revealed that the MIC of tiamulin and tilmicosin (μg/ml) was 0.1 and 0.05; respectively. In-vivo evaluation of tiamulin and tilmicosin denoted that there were significant (p